2019
DOI: 10.1039/c9nj02549a
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the electronic transitions of mixed valence polyoxovanadoborates [V12B18O60]: from an experimental to a theoretical understanding

Abstract: New insights in the electronic properties of mixed-valence polyoxovanadoborate clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The strong band features below 350 nm can be attributed to the ligand to metal charge transfer (LMCT) of O → M. The broad bands in the region of 500–800 nm correspond to a combination of d → d transitions of the metal ions and intervalence transitions of conjugated vanadium systems . The spectra of 1 – 4 are consistent with the spectra of mixed-valence oxovanadium complexes, whose maximum absorptions are in the region of 500–800 nm varying with V­(V)/V­(IV) ratios. , In addition, the deep colors that are intimately connected with the interatomic oxidation–reduction tendencies are also observed in 1 – 4 , implying a mixture of V­(IV) and V­(V) centers. In Figure S17, the electronic spectrum of 2 -Fe-O 2 shows a weakened and broadened band below 350 nm after adsorption, which corresponds to a change in the ligand to metal charge transfer of O → M.…”
Section: Resultsmentioning
confidence: 53%
“…The strong band features below 350 nm can be attributed to the ligand to metal charge transfer (LMCT) of O → M. The broad bands in the region of 500–800 nm correspond to a combination of d → d transitions of the metal ions and intervalence transitions of conjugated vanadium systems . The spectra of 1 – 4 are consistent with the spectra of mixed-valence oxovanadium complexes, whose maximum absorptions are in the region of 500–800 nm varying with V­(V)/V­(IV) ratios. , In addition, the deep colors that are intimately connected with the interatomic oxidation–reduction tendencies are also observed in 1 – 4 , implying a mixture of V­(IV) and V­(V) centers. In Figure S17, the electronic spectrum of 2 -Fe-O 2 shows a weakened and broadened band below 350 nm after adsorption, which corresponds to a change in the ligand to metal charge transfer of O → M.…”
Section: Resultsmentioning
confidence: 53%
“…The vanadyl stretching band ( V-Ot ) appears at c.a. 920 cm -1 for all studied compounds and in the expected range [9,10,14,[16][17][18][19]21,22,26,[27][28][29][30][31][32]37,[71][72][73]. However, compounds 2 and 3 show a broad band with a shoulder, while compound 1 shows a narrower band than the former ones (Figure 3).…”
Section: Infrared Spectroscopymentioning
confidence: 95%
“…Recent studies of vanadoborates related to the conductivity of these materials show the importance of the nature of the crystalline packing and all interactions present in it [5][6][7]. The reported VBO structures are mainly composed by six, ten and twelve vanadium centres [2,6], namely the {V 6 -type} clusters: {V 6 B 20 O 50 H n } (n=0, 6,8,12) [8][9][10][11] and {V 6 B 22 O 54 H 10 } [12]; the {V 10 -type} clusters: {V 10 B 28 O 74 H n } [13] and {V 10 B 28 O 74 H n } (n=4, 8) [14,15]; the {V 12 i -type} clusters: {V 12 [11,20,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], and the {V 12 iii -type} clusters: {V 12 B 32 O 84 H 8 } [38,39]. The most interesting feature of the boron rich structures {V 6 -type}, {V 10 -type} and {V 12 iii -type} is their central oxo-vanadium ring formed by penta-coordinated vanadium units [VO 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…1, the X-ray crystal structure has revealed that CO serves as a Z 1 ,m 2 -bridging ligand coordinated to Fe2 and Fe6 by replacing a sulfur atom (S2B) (PDB entry: 4KTV), 15,16 and the second CO terminally binds to Fe6 (PDB entry: 7JRF). 16 Recently, N 2 or N 2 -derived species (PDB entry: 6UG0) The bond valence method originated from Pauling's rule in 1929 21 and developed historically, and is commonly applied in inorganic chemistry [22][23][24][25] and metalloenzyme fields. [26][27][28] It is a classic and valid approach to assess the charge between metal atoms and its bound coordinated atoms, which has been proved as an effective method to evaluate the electron density in a delocalized system.…”
Section: Introductionmentioning
confidence: 99%
“…The bond valence method originated from Pauling's rule in 1929 21 and developed historically, and is commonly applied in inorganic chemistry 22–25 and metalloenzyme fields. 26–28 It is a classic and valid approach to assess the charge between metal atoms and its bound coordinated atoms, which has been proved as an effective method to evaluate the electron density in a delocalized system.…”
Section: Introductionmentioning
confidence: 99%